Characterization of a strain of quaranfil virus isolated from soft ticks in India. Is quaranfil virus an unrecognized cause of disease in human and animals? - Mourya, Devendra T.; Yadav, Pragya D.; Nyayanit, Dimpal A.; Majumdar, Triparna D.; Jain, Shilpi; Sarkale, Prasad; Shete, Anita (Heliyon, 2019)
The soft ticks collected during a field survey in Karnataka state, India, in 1983, yielded a novel virus isolate, which caused mortality in an infant mouse upon inoculation. Attempts at characterizing the virus using the conventional methods were unsuccessful, which prompted us to study it by Next-Generation Sequencing (NGS). This virus isolate was obtained from the viral repository of National Institute of Virology, and an initial virus stock was prepared as a mouse brain homogenate. The virus stock showed cytopathic effects in different cell-lines and was used in NGS. Based on the complete genome sequence, obtained using de novo and reference mapping approach, the virus isolate was identified as a Quaranfil virus (QRFV) belonging to the family Orthomyxoviridae, genus Quaranjavirus. The genome size of the virus is 11,427 nucleotides which consist of 6 segments encoding six proteins. Homology analysis suggested this isolate as similar to QRFV of Afghanistan. In silico analysis showed the HA protein secondary structure to be a class III penetrance similar to Thogotovirus. QRFV was first isolated in 1953 from ticks [Cairo, Egypt] and subsequently reported from other geographical areas. This is the first report describing the presence of QRFV from India. This discovery emphasizes the need for investigating mild febrile illness cases with influenza-like symptoms, particularly in the area of high risk for tick bites.